Dinamika penerapan kurikulum merdeka dalam pembelajaran Qur’an Hadis di Madrasah berbasis keislaman - Muhamad Ariel Syahroni; Akhsinatul Kumala (Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the dynamics of implementing the Merdeka Curriculum in Qur’an and Hadith instruction at Islamic-based madrasahs. The background of this study is rooted in a shift in the learning paradigm that emphasizes a student-centered approach, learning flexibility, and the strengthening of religious character. The research method employed is a qualitative approach using a case study design. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis utilized data reduction, data presentation, and drawing conclusions through triangulation to ensure data validity. The research findings indicate that the implementation of the Merdeka Curriculum in Qur’an and Hadith instruction is carried out through learning-outcome-based planning, interactive and participatory teaching methods, and assessments that cover both cognitive and affective aspects. The dynamics that emerged include supporting factors such as teacher readiness, institutional support, and a religious environment, as well as inhibiting factors such as time constraints, differences in student abilities, and teacher adaptation to curriculum changes. This study contributes to understanding the implementation of the Merdeka Curriculum in religious studies and serves as a reference for the development of more contextual and effective learning in madrasahs.